2014
DOI: 10.1002/chem.201400333
|View full text |Cite
|
Sign up to set email alerts
|

Amine‐Catalyzed Enantioselective 1,3‐Dipolar Cycloadditions of Aldehydes to C,N‐Cyclic Azomethine Imines

Abstract: Amine-catalyzed enantioselective 1,3-dipolar cycloadditions of aldehydes to C,N-cyclic azomethine imines were developed. The reactions between diversely substituted C,N-cyclic azomethine imines and aldehydes proceeded smoothly in the presence of chiral prolinol silyl ether catalyst and gave the C-1-substituted tetrahydroisoquinolines in a highly stereoselective manner. These tetrahydroisoquinolines could be efficiently transformed to several other useful polycyclic frameworks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…50 Different type of dipolarophiles have been investigated under thermal conditions with azomethine imines 166 derived from unsubstituted 165, among them, acetylenic sulfones, 106 arynes, 107 β-nitrostyrenes, 108 cyclic vinyl sulfones, 109 and trifluoroethylidene malonates. 110 In the case of using azlactones 189 as dipolarophiles, a [3+2] cycloaddition, followed by a rearrangement at room temperature, gave the pyrazolopirazolone derivatives 190 (Scheme 71).…”
Section: Scheme 70 Synthesis Of Polyoxygenated Diazatriquinane 188 VImentioning
confidence: 99%
“…50 Different type of dipolarophiles have been investigated under thermal conditions with azomethine imines 166 derived from unsubstituted 165, among them, acetylenic sulfones, 106 arynes, 107 β-nitrostyrenes, 108 cyclic vinyl sulfones, 109 and trifluoroethylidene malonates. 110 In the case of using azlactones 189 as dipolarophiles, a [3+2] cycloaddition, followed by a rearrangement at room temperature, gave the pyrazolopirazolone derivatives 190 (Scheme 71).…”
Section: Scheme 70 Synthesis Of Polyoxygenated Diazatriquinane 188 VImentioning
confidence: 99%
“…There were, however, many successful predictions. For example, CSD entry QIXHUC (Li et al, 2014) was successfully used as a shape analogue for CSD entry REDNIX (Steiner et al, 1997). Both are Z 0 = 2, Z r = 1 structures in the space group P2 1 containing elongated molecules forming dimers between the crystallographically independent molecules that are related to one another by approximate 2 1 screw axes.…”
Section: Tablementioning
confidence: 99%
“…Scheme 17 Thiourea-catalyzed IED 1,3-dipolar cycloaddition of C,Ncyclic azomethine imines with azlactones Proline derivatives have also been used as asymmetric organocatalysts in the reaction of aldehydes/ketones with C,N-cyclic methine imines, as one of the strategies for nucleophile activation. In 2014, enantioselective 1,3-dipolar cycloadditions of aldehydes to C,N-cyclic azomethine imines were developed by Wang's group 51 and Alemán's group 52 respectively. Wang and co-workers reported that various substituted C,N-cyclic azomethine imines and aldehydes underwent IED [3+2] cycloaddition smoothly in the…”
Section: Ied [3+2] Cycloaddition Of Cn-cyclic N′-acyl Azomethine Iminesmentioning
confidence: 99%
“…presence of chiral prolinol silyl ether catalyst C14 and gave C 1 -substituted THIQs 40 with high stereoselectivities (Scheme 18a). 51 The formation of an intermediate enamine was the key step to this reaction. Without the addition of acetic acid, no desired cycloaddition adduct was observed.…”
Section: Short Review Synthesismentioning
confidence: 99%